The relationship between childhood adversities and complex posttraumatic stress symptoms: a multiple mediation model. Issue 1 (1st January 2021) - Guo, Tianyou; Huang, Liuyue; Hall, Daniel L.; Jiao, Can; Chen, Si-Tong; Yu, Qian; Yeung, Albert; Chi, Xinli; Zou, Liye
ABSTRACT: Background : There is a growing research literature on complex posttraumatic stress disorder (CPTSD), yet studies that focused on Chinese populations are still limited. Accumulating evidence showed that adverse childhood experiences (ACEs) are associated with a higher likelihood of CPTSD symptoms, but potential mediating roles of self-kindness and self-judgement on the ACEs-CPTSD relationship remain understudied. Objective : The purpose of this study was to first examine the relationship between ACEs and CPTSD among Chinese college students, and then to test the mediating role of self-kindness and self-judgement on the ACEs-CPTSD relationship. Method : The study included 1361 college students for an online survey in May 2020. Demographic variables (e.g. age, gender, having sibling[s] or not, residence, family structure, and subjective socioeconomic status), ACEs, self-compassion (self-kindness and self-judgement subscales), and CPTSD symptoms were assessed. After controlling for demographic variables, a series of structural equation models tested the mediation hypothesis: indirect effects of self-kindness and self-judgement on the relationship between ACEs and CPTSD symptom. Results : ACEs of College students were positively associated with more severe CPTSD symptoms (posttraumatic stress disorder and disturbances in self-organization symptoms). Furthermore, these direct pathways were mediated by decreased self-kindness and increased self-judgement. Conclusions : Findings have substantial theoretical and treatment implications, including the two critical targets (i.e. lowering self-judgement and raising self-kindness) when treating complex PTSD. HIGHLIGHTS: College students' ACEs were positively associated with more severe CPTSD symptoms, and these direct pathways were mediated by decreased self-kindness and increased self-judgement.